PENGARUH FIRM SIZE DAN PROFITABILITAS TERHADAP HARGA SAHAM PADA PERUSAHAAN PERBANKAN DI BURSA EFEK INDONESIA PERIODE 2018-2022 - Pradhana, Moh Yusuf (Jurnal Ekonomika dan Manajemen, 2024)
The aim of this research is to determine the effect of firm size and profitability on share prices in banking companies on the Indonesia Stock Exchange for the 2018-2022 period. The approach used in this research is a quantitative approach. This type of research is explanatory research. The population in this research is 46 BEI banking companies for the 2018-2022 period. Sample selection was used using a purposive sampling method, so that the sample in this study was 34 BEI banking companies for the 2020-2022 period. The analysis technique used is multiple linear regression. The results of this research state that company size has a significant positive influence on share prices, and profitability has a significant positive influence on share prices so it can be concluded that company size and profitability have an influence on share prices both partially and simultaneously.